If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 5 = 4x + -4 Reorder the terms: 5 + x = 4x + -4 Reorder the terms: 5 + x = -4 + 4x Solving 5 + x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + x + -4x = -4 + 4x + -4x Combine like terms: x + -4x = -3x 5 + -3x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + -3x = -4 + 0 5 + -3x = -4 Add '-5' to each side of the equation. 5 + -5 + -3x = -4 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = -4 + -5 -3x = -4 + -5 Combine like terms: -4 + -5 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 15=-2+n | | 615=15n+75 | | -8=p-10 | | 0=a-18 | | 38-13=5(x-1) | | 28x-7y=-7 | | 0.5*x+0.25*x=16 | | 5x+10=28-x | | n-20=-10 | | x+22+4x=-46-4x-49 | | 8x+5=6(x+6) | | 10a-3a= | | b-1=-4 | | 6x+39=14x-23 | | 21-r=7 | | 5(x-1)+2x=7(x-3)+4 | | x-12=-41 | | 24-6x=15+3x | | 4-5y=6(3-2y) | | 8=19+x | | 3(2x-3)+11=8 | | 3x+36=8-4x | | -6=k-11 | | 5x-3=6x+9 | | 3(6-0.0033333333y)+y=18 | | 3=3a+18 | | 11x-14=107 | | 11x=97 | | 3(x+9)+129=180 | | 4(3u+5)=8u+14 | | 8(a+b)+3z=-9 | | -13+v=-28 |